Reactivity of a Sterically Unencumbered α‐Borylated Phosphorus Ylide towards Small Molecules. Issue 52 (23rd August 2019) - Radius, Michael; Sattler, Ewald; Berberich, Helga; Breher, Frank
Abstract: The influence of substituents on α‐borylated phosphorus ylides (α‐BCPs) has been investigated in a combined experimental and quantum chemical approach. The synthesis and characterization of Me3 PC(H)B( i Bu)2 (1 ), consisting of small Me substituents on phosphorous and i Bu residues on boron, is reported. Compound 1 is accessible through a novel synthetic approach, which has been further elucidated through DFT studies. The reactivity of 1 towards various small molecules was probed and compared with that of a previously published derivative, Ph3 PC(Me)BEt2 (2 ). Both α‐BCPs react with NH3 to undergo heterolytic N−H bond cleavage. Different di‐ and trimeric ring structures were observed in the reaction products of 1 with CO and CO2 . With PhNCO and PHNCS, the expected insertion products [Me3 PC(H)(PhNCO)B( i Bu)2 ] and [Me3 PC(H)(PhNCS)B( i Bu)2 ], respectively, were isolated. Abstract : Free to move : A sterically unencumbered α‐borylated phosphorus ylide (α‐BCP) Me3 PC(H)B( i Bu)2 (1 ) has been synthesized, characterized, and investigated with the aid of DFT calculations. Compound 1 reacts with various small molecules, such as NH3, CO, and CO2, and heterocumulenes PhNCX (see figure).